2015
DOI: 10.1242/jcs.174664
|View full text |Cite
|
Sign up to set email alerts
|

Rabaptin5 is recruited to endosomes by Rab4 and Rabex5 to regulate endosome maturation

Abstract: Rab GTPases control membrane identity, fusion and transport by interaction with effector proteins. Effectors that influence the activation-inactivation cycle of their own or other Rab proteins contribute to the timely conversion of Rab membrane identities. Rab5 and its effector rabaptin5 (Rbpt5, also known as RABEP1) are generally considered the prime example for a positive-feedback loop in which Rab5-GTP recruits Rbpt5 in complex with Rabex5 (also known as RABGEF1), the GDP/GTP exchange factor of Rab5, to ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 42 publications
2
52
0
Order By: Relevance
“…12 Endosomes traffic receptors such as VEGFR2 to sites involved in downstream signaling, lysosomes, or back to the cell membrane. 1315 We thus examined EE in pial membrane of Rabep2 − / − mice at E14.5 when collaterogenesis is underway. Endosome diameter was larger in Rabep2 − / − while density was similar (Figure 5A–C).…”
Section: Resultsmentioning
confidence: 99%
“…12 Endosomes traffic receptors such as VEGFR2 to sites involved in downstream signaling, lysosomes, or back to the cell membrane. 1315 We thus examined EE in pial membrane of Rabep2 − / − mice at E14.5 when collaterogenesis is underway. Endosome diameter was larger in Rabep2 − / − while density was similar (Figure 5A–C).…”
Section: Resultsmentioning
confidence: 99%
“…20 Their function was proposed to be the regulation of AP-1 or GGA dependent vesicle transport at endosomes. 16,20 In the recent study by K€ alin et al, 21 …”
Section: Feedforward Instead Of Feedback For Rab5 Activationmentioning
confidence: 95%
“…The contribution of Rabex5 to Rabaptin5 recruitment could be localized to its ubiquitin interaction domain, which recognizes ubiquitinated endocytic cargo. 10,22 The second requirement for Rabaptin5 EE recruitment was found to be Rab4-GTP 21 : siRNA silencing of Rab4 or deletion of both CC1-1 and CC1-2 abolished membrane binding, while individual deletion of either one coiled-coil domain did not. In vitro, Rabaptin5 lacking CC1-1 was still able to bind Rab4-GTP, whereas no interaction could be detected without CC1-2, suggesting a low affinity site at CC1-1 or interaction with another component that itself is dependent on Rab4.…”
Section: Feedforward Instead Of Feedback For Rab5 Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammalian cells, Rabex-5 is recruited to early endosomes through its N-terminal ubiquitin-binding domain, where Rabaptin5, a Rabex-5-binding partner, relieves autoinhibition of Rabex-5 thereby yielding an active form of Rab5 (Mattera and Bonifacino, 2008;Zhang et al, 2014). Although a feedback mechanism in which Rab5 recruits Rabaptin5 that is associated with Rabex-5 and enhances Rab5 activation has been suggested, a recent study has shown that the membrane localization of Rabaptin5 depends on Rab4 and Rabex-5, not on Rab5 (Kälin et al, 2015). On the other hand, Gapex-5 (also called hRME-6), which was originally identified in C. elegance rme-6 mutants and exhibits GEF activity toward Rab5 and Rab22B/31, localizes on clathrincoated vesicles and regulates Rab5-mediated uncoating of AP2 from clathrin-coated vesicles in mammalian cells Lodhi et al, 2007;Semerdjieva et al, 2008).…”
Section: Rab-gefs and Their Target Rabsmentioning
confidence: 99%